CAN WE TALK ABOUT DIGITAL ECONOMY TAXATION WITHOUT IMPROVED ADMINISTRATIVE COOPERATION BETWEEN COUNTRIES? - Ivanov, Iva (Pravni zapisi, 2022)
Finding the right rules for taxation of corporate income in digital economy has been at the centre of attention of international tax community. Three proposals have received most attention, even though it is still uncertain whether any of them would be elected as a final solution. What these proposals show us is that in order to adopt new rules for taxation of digital economy, it is necessary to provide a functional global environment where information would be readily available and where countries would provide assistance in tax collection. However, existing mutual assistance instruments fall short of that. In this paper it is argued that current political momentum around the need to reach an international consensus should be used to enhance mutual assistance mechanisms. It is argued that CRS should become main global instrument for automatic exchange of information, or at least that CRS and FATCA rules should be harmonised so that there are no differences between them. Furthermore, it is argued that all countries should start providing assistance in tax collection based on OECD MAC. And secondly, it is argued that programs for technical assistance and capacity building offered by the OECD should be expanded so that more countries have access to them and that more resources are dedicated to each country.
Keywords: digital economy taxation; automatic exchange of information; FATCA; CRS; DAC; OECD MAC; assistance in tax collection